EFL TEACHERS’ ASSESSMENT LITERACY: IMPACT OF EXPERIENCE AND ACADEMIC ATTAINMENT - Muhammad, Fryda Hama Najib (Sulaimani Journal for Humanities, 2026)
Assessment plays a key role in teaching process; therefore, it receives academic attention in recent years. This research utilizes a survey- based approach to evaluating EFL teachers’ fundamental knowledge of assessment. The questionnaire, Classroom Assessment Literacy Inventory (CALI), based on the seven standards of assessment competence for educational assessment of students, established by the American Federation of Teachers (AFT), National Council on Measurement in Education (NCME) and National Education Association (NEA) (1990). The paper tries to investigate whether teaching experience or academic achievement affects assessment literacy level. The data is collected from 61 EFL teachers in Sulaimani, Iraq. The findings show that the overall performance is inadequate and neither academic attainment nor classroom experience grant significant difference in EFL teachers’ assessment literacy in the context of this research. However, the study concludes by recommending various methodological approaches in the field to explore the nexus between teachers’ knowledge and professional classroom practice.
Keywords: EFL teachers; Assessment literacy; Teacher knowledge; Testing